2018
DOI: 10.1002/bmc.4416
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive and rapid determination of tacrolimus in peripheral blood mononuclear cells by liquid chromatography–tandem mass spectrometry

Abstract: After solid organ transplantation, tacrolimus is given to prevent rejection. Therapeutic drug monitoring is used to reach target concentrations of tacrolimus in whole blood. Because the site of action of tacrolimus is the lymphocyte, and tacrolimus binds ~80% to erythrocytes, the intracellular tacrolimus concentration in lymphocytes is possibly more relevant. For this purpose, we aimed to develop, improve and validate a UPLC–MS/MS method to measure tacrolimus concentrations in isolated peripheral blood mononuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 19 publications
1
23
0
Order By: Relevance
“…There was no correlation between tacrolimus concentrations in whole blood and PBMCs at 1.5 h post-dose. Evidence supporting this finding is scarce and conflicting; some papers do report a correlation in transplantation patients [19,20], whereas other papers do not [21,22]. Tacrolimus levels in T cells, on the other hand, did correlate significantly with whole blood concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no correlation between tacrolimus concentrations in whole blood and PBMCs at 1.5 h post-dose. Evidence supporting this finding is scarce and conflicting; some papers do report a correlation in transplantation patients [19,20], whereas other papers do not [21,22]. Tacrolimus levels in T cells, on the other hand, did correlate significantly with whole blood concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Whole blood and intracellular tacrolimus concentrations were measured using a Waters Acquity UPLC–MS/MS system by the Department of Hospital Pharmacy, Erasmus Medical Center, as described previously [19].…”
Section: Methodsmentioning
confidence: 99%
“…The authors reported a good correlation between intrahepatic or intra-PBMC concentrations of TAC, and an histological rejection score determined at day-7 posttransplantation whereas no association was found with whole blood TAC concentrations. Besides, the relationship between TAC whole blood concentrations and TAC concentrations in PBMC have been studied in various organ transplant patients [5][6][7][8][9][10][11]. These works were concordant to report a poor correlation between trough whole blood and trough intracellular concentrations, meaning that monitoring TAC in its target cell could be a better surrogate marker of its pharmacological effect.…”
Section: Introductionmentioning
confidence: 97%
“…Tac concentration in lymphocytes could be an appropriate matrix to monitor Tac treatment. [175][176][177][178] In a study by Capron et al, 179 intracellular Tac concentration was correlated with both the development and severity of rejection after liver transplantation. However, the authors of this review think that at present, there is insufficient evidence to make recommendations regarding the optimal matrix for TDM of Tac during pregnancy.…”
Section: Implications For Tdmmentioning
confidence: 98%